Borealis Festival, Bergen. (28th September 2016) - Gottschalk, Kurt
Abstract : It wouldn't be the worst idea if Anthony Braxton's Composition No. 58 were used to kick off every music festival. In any event, it's hard to think of a fanfare more fitting for the common fan, whether of classical, jazz or experimental rock. It could, for example, quite easily be followed by a piece of Mauricio Kagel's instrumental theatre or a parade by the Sun Ra Arkestra or the precisely played experimental excursions of the Brooklyn avant-rock outfit Zs.